Shotgun metagenomic sequencing analysis of ocular surface microbiome in Singapore residents with mild dry eye - Tong, Louis; Constancias, Florentin; Hou, Aihua; Chua, Song Lin; Drautz-Moses, Daniela I.; Schuster, Stephan Christoph; Yang, Liang; Williams, Rohan B. H.; Kjelleberg, Staffan (Frontiers in Medicine, 2022)
The ocular surface microbiome has implications for ocular surface inflammation and immunology. Previous shotgun metagenomics analyses were performed in China, showing results that differed according to environment and age. Patients with Sjogren's syndrome were reported to have altered conjunctival microbiome, but such studies have not been done in milder dry eye. The aim of this study is to describe the conjunctival microbiome in people with mild dry eye in Singapore. Samples were collected from 12 participants with mild dry eye and 12 age-matched comparison participants recruited from Singapore National Eye Centre (SNEC) clinics. Shotgun metagenomic sequencing analysis was employed to evaluate the conjunctival microbiome composition. Proteobacteria formed the predominant phylum in the conjunctiva. As in a study from a coastal city in China, Achromobacter spp. was numerically most abundant. Compared to age-matched controls, the conjunctival microbial composition in mild dry eye was similar. Several microorganisms, including Streptococcus spp. increased in representation with age, and the abundance of Staphylococcus correlated with Schirmer readings. In addition, when cultured corneal epithelial cells were exposed to three strains of Achromobacter xylosoxidans, cytokines such as TNF- and IL-6 were upregulated in the cell lysates and supernatants. Our results suggest that age is an important factor that affects composition of the conjunctival microbiome, and relative abundance of specific microorganism may vary according to the environment of the human host.